A macro-anatomic study of white pelican (pelecanus onocrotalus) hearts - Atila Yoldaş; M. Orhun Dayan (Eurasian Journal of Veterinary Sciences)
The aim of this study is to reveal the macroanatomy of the heart valves of the 5 white pelicans. The left atrioventricular valve consists of one septal and two parietal leaves (cuspis). The left atroventricular valve having a muscular structure was attached to the parietal face of the atrioventricular orifice and its free edge, flapped into the right ventricle, was fixed to the septum by a short left septal attachment, and gave attachment to rough parietal wall of the ventricle by a thick muscular stalk. The rectangle shaped valves of the right atrioventricular ventricle had chordae tendineae-likestructures near the septal edge of the valve and external wall, whose free edges were linked to the ventricle wall by chordae tendineae. The aortic orifice is encircled by the aortic valve, composed of three semilunar cusps; right, left and septal. The pulmonary valve consists of three cusps. In all examined materials, the semilunar cusps in the central part of the free margin of each cusp had the semilunar valve nodules. The minor anatomic changes observed in this work may be resulted from differences of species.